Differences of Enzymatic Activity During Composting and Vermicomposting of Sewage Sludge Mixed With Straw Pellets - Hanc, Ales; Dume, Bayu; Hrebeckova, Tereza (Frontiers in Microbiology, 2022)
The study aims were focused on profiling eight hydrolytic enzymes by fluorescence method using a multifunctional modular reader and studying the proportion of basic microorganism groups during composting and vermicomposting of sewage sludge mixed with straw pellets in several proportions (0, 25, 50, 75, and 100%). The greatest decrease in enzymatic activity occurred in the first half of composting and vermicomposting. After 4 months of these processes, the least enzymatic activity was observed in the sludge with 50% and also 25% straw addition, indicating that straw is an important means for the rapid production of mature compost from sewage sludge. Enzymatic activity was usually less in the presence of earthworms than in the control treatment because some processes took place in the digestive tract of the earthworm. For the same reason, we observed reduced enzyme activity during fresh feedstock vermicomposting than precomposted material. The final vermicompost from fresh feedstocks exhibited less microbial biomass, and few fungi and G− bacteria compared to precomposted feedstock. The enzymatic activity during composting and vermicomposting of sewage sludge and their mixtures stabilized at the following values: β-D-glucosidase—50 μmol MUFG/h/g dw, acid phosphatase—200 μmol MUFP/h/g dw, arylsulphatase—10 μmol MUFS/h/g dw, lipase—1,000 μmol MUFY/h/g dw, chitinase—50 μmol MUFN/h/g dw, cellobiohydrolase—20 μmol MUFC/h/g dw, alanine aminopeptidase—50 μmol AMCA/h/g dw, and leucine aminopeptidase—50 μmol AMCL/h/g dw. At these and lesser values, these final products can be considered mature and stable.